Meditasi Buddha Theravada Dalam Perspektif Mahasi Sayadaw - Eka Gusti; Eriz Ghazanfer (Jurnal Budi Pekerti Agama Buddha, 2023)
In this world there are also people who behave well, are able to control themselves, always speak politely and kindly, like to comfort people who are grieving, like to help people who are in trouble, like to help people who are in trouble, and various other types of virtue. In today's society there are also children who are devoted to their parents, who serve their parents well, who always obey their parents' advice, who always want to listen to their parents' complaints. In today's society, it is common to find people who experience stress, depression, and then commit suicide. On Friday, March 17 2017 morning, a man in Jagakarsa, South Jakarta, committed suicide. Based on average statistics, in a day there are at least two to three people who commit suicide in Indonesia. The Central Statistics Agency (BPS) recorded at least 812 suicide cases throughout Indonesia in 2015. This figure is recorded by the police. The real figures on the ground could be even higher.